Effect of seed priming on growth and yield parameters of maize - Dawadi, Ebha (2023)
Maize is the principal food crop of people living in inner Terai region of Nepal. This region receives comparatively less rainfall that results in insufficient seedling emergence and inappropriate stand establishment. So seed priming is simple cost-effective and easily implementable technique that ensures better germination and crop establishment as well as enhancing production. The study was conducted from February 2021 to May 2021 in farmer’s field, Hadiya-9, Udaipur to examine how the growth and yield parameters were affected by seed priming. The experiment was laid out in single factor randomized complete block design with 3 replications and 7 treatments namely T1: control, T2: hydro priming for 6 h, T3: hydro priming for 12 h, T4: zinc sulphate priming (0.5 % for 12h), T5: zinc sulphate priming (1 % for 12 h) and T6= zinc sulphate priming (2 % for 12 h), T7= cow urine priming (2 times dilution). Results showed that there was a significant effect on the germination percentage, germination index, days to 100 % germination, leaf number, days to tasseling and silking, cob length, kernel per cob, cob girth, total plant population per hectare, 1000 grain weight, grain yield, biological yield and harvest index of corn. Hydro priming for 18 h (T3) and Cow urine priming 2.5 times dilution for 12 h (T7) were found to be most effective priming solution showing higher influence in germination percentage, germination index, days to 100 % germination, leaf number, days to tasseling and silking, plant height, cob length, kernel per cob, total plant population per hectare and harvest index. To sum up, the result indicate that the findings suggest that using hydro priming for 18 h and cow urine priming 2.5 times dilution for 12 h as seed priming agents can significantly improve the growth and yield parameters of corn. This study clarifies the potential of several compounds used during seed priming to improve corn development and production.